The university versus region effect: A variance decomposition of academic spin‐off performance - Mokhtar, Julia; Knockaert, Mirjam; Vanacker, Tom; Bliese, Paul (Strategic Management Journal, 2026)
Abstract Research Summary Academic spin‐off (ASO) performance has been studied in relation to either specific university‐level or regional‐level characteristics. However, ASOs originate from universities, which are embedded in regional ecosystems. This nested structure can create an attribution problem when either level is studied in isolation. Consequently, the relative importance of these two different levels for ASO performance has remained ambiguous. To address this ambiguity, we rely on multi‐level modeling and use a novel, hand‐collected dataset of 3164 ASOs founded between 2010 and 2019 from 212 universities nested within 99 European regions. We find that the region effect matters for about 27% for Return on Assets and 16% for Sales, whereas the university effect is negligible. Our study contributes to research at the nexus of academic entrepreneurship and variance decomposition in strategy. Managerial Summary Academic spin‐offs (ASOs) bring innovations from the university to the market, thereby potentially generating new sales, employment, and value. However, once formed, their performance prospects vary significantly, and understanding this variance is important for entrepreneurs and policymakers alike. Our findings from a new European dataset reveal that the region effect matters for ASO performance, but the university effect is negligible. This evidence does not imply that universities lack importance; rather, it suggests that universities in a region may have a collective impact that diffuses into regional resources and networks. Our evidence highlights the importance of fostering a supportive regional ecosystem.